Attitude of Nonlanguage Program Students Toward the Indonesian Language at the Universitas Mulawarman - Mulawarman, W G; Yankynandasari, L (KnE Social Sciences, 2018)
The purpose of this study was to describe the attitude of the nonlanguage program students of the Universitas Mulawarman to the Indonesian language. Nonlanguage program students were required to take Bahasa Indonesia as a General Compulsory Subject (MKWU) in order for students to have Indonesian language skills, both spoken and written. The data collection stage was carried out by using a questionnaire, observation, documentation, and interviews. The Likert scale technique was used to analyze the quantitative data while the qualitative data in the form of speech was analyzed using the speech act model of Dell Hymes and the language error analysis technique to analyze the data in paper form. The results showed that the language attitude of the students at the FKIP Universitas Mulawarman toward the Indonesian language tends to be negative. Their tendency to underestimate and ignore Indonesian grammar was visible in the spoken and written language they used. This was based on the results of respondents’ questionnaires as evidenced by the presence of code mixing in all speech and morphological and syntactical errors in all the written work of the respondents. Keywords: language attitude, nonlanguage program students, sociolinguistics